Hypoxia induces senescence of bone marrow mesenchymal stem cells via altered gut microbiota - Junyue Xing (Nature Portfolio, 2018)
Systemic chronic hypoxia is a feature of many diseases and may influence the communication between bone marrow and gut microbiota. Here, the authors show that chronic hypoxia predisposes bone marrow stem cells to premature senescence, which may be due to gut dysbiosis and gut microbiota-derived d-galactose accumulation.